2005
DOI: 10.1105/tpc.104.029447
|View full text |Cite
|
Sign up to set email alerts
|

The MutantcrispaReveals Multiple Roles forPHANTASTICAin Pea Compound Leaf Development

Abstract: Pinnate compound leaves have laminae called leaflets distributed at intervals along an axis, the rachis, whereas simple leaves have a single lamina. In simple-and compound-leaved species, the PHANTASTICA (PHAN) gene is required for lamina formation. Antirrhinum majus mutants lacking a functional gene develop abaxialized, bladeless adult leaves. Transgenic downregulation of PHAN in the compound tomato (Solanum lycopersicum) leaf results in an abaxialized rachis without leaflets. The extent of PHAN gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 63 publications
4
94
2
Order By: Relevance
“…However, some differences were found: the signal for LjKN1 was always stronger and in much restricted area near the central zone of SAM, but the one for LjKN3 was generally weaker and more dispersed. No LjKN1 and LjKN3 transcripts were detected in the compound leaf primordia or leaflet primordia at any stage, consistent with previous reports about no expression of KNOXI genes in the compound leaf primordia in pea [24,30]. On the other hand, we failed to detect the expression of LjKN2 in any tissues at both vegetative and reproductive stages by RNA in situ hybridization.…”
Section: Overexpression Of Ljphana and Ljphanb In Arabidopsissupporting
confidence: 92%
See 3 more Smart Citations
“…However, some differences were found: the signal for LjKN1 was always stronger and in much restricted area near the central zone of SAM, but the one for LjKN3 was generally weaker and more dispersed. No LjKN1 and LjKN3 transcripts were detected in the compound leaf primordia or leaflet primordia at any stage, consistent with previous reports about no expression of KNOXI genes in the compound leaf primordia in pea [24,30]. On the other hand, we failed to detect the expression of LjKN2 in any tissues at both vegetative and reproductive stages by RNA in situ hybridization.…”
Section: Overexpression Of Ljphana and Ljphanb In Arabidopsissupporting
confidence: 92%
“…Previous studies showed PHAN-KNOXI interaction in pea is similar to that in Arabidopsis [30]. To investigate whether it is the same case in L. japonicus, we isolated KNOXI genes and examined their expression patterns by RNA in situ hybridization.…”
Section: Expression Patterns Of Knoxi Genes In L Japonicusmentioning
confidence: 90%
See 2 more Smart Citations
“…rs2 encodes a myb-type protein that represses KNOX expression in the lateral organs of several plant species with both simple leaves (such as maize, Arabidopsis and snapdragon) and compound leaves (such as pea and the Arabidopsis relative C. hirsuta). Collectively, these are called ARP proteins [ASYMMETRIC LEAVES1 (AS1) in Arabidopsis, Rough sheath2 in maize, PHANTASTICA in snapdragon] (Byrne et al, 2000;Hay and Tsiantis, 2006;Tattersall et al, 2005;Timmermans et al, 1999;Tsiantis et al, 1999). In these plants, ARP and KNOX gene expression distinguishes leaf founder cell from meristem cell fate in the shoot apex.…”
Section: Box 2 Knox Protein Traffickingmentioning
confidence: 99%